The Interconnection between Ecology and Direct Democracy in Alternative Food Networks - Tzekou, Eirini-Erifyli; Gritzas, Giorgos (PARTECIPAZIONE E CONFLITTO, 2023)
The literature of Alternative Food Networks has engaged with ecological practices as well as decision-making. Nevertheless, it usually approaches ecology and democracy in Alternative Food Networks separately or as a sum of good practices, thus neglecting their interaction. The present article proposes a holistic approach of these practices under the lens of degrowth and post-development. Ecology and democracy are at the epicenter of degrowth and post-development discourse which offer a coherent framework to study social change. Based on the data drawn from a field survey including 43 semi-structured interviews with members of 13 Alternative Food Networks and a nine-month participant observation in the city of Thessaloniki, Greece, the article studies the interplay between ecological practices and direct democratic decision-making. The study brings to the foreground the way Alternative Food Networks negotiate environmental sustainability as well as the complementarities and conflicts between their different goals and strategies. Consequently, it highlights the need for incorporating holistic discourses such as degrowth and post-development into the study of Alternative Food Networks.